1999
DOI: 10.1007/bf00992870
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient budgets and biogeochemistry in an experimental agricultural watershed in Southeastern China

Abstract: Abstract. During a two-year field study, an annual nutrient budget and cycles were developed for a small agricultural watershed. The study emphasized the integrated unit of the watershed in understanding the biogeochemistry. It was found that the total nutrient input was 39.1 x 104 kg nitrogen and 3.91 x 104 kg phosphorus in the year 1995, of which the greatest input of nutrients to the watershed was chemical fertilizer application, reaching 34.7 x 104 kg (676 kg/ha) nitrogen and 3.88 x 104 kg (76 kg/ha) phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 17 publications
1
47
0
Order By: Relevance
“…The sites located close to rural residential area showed higher mean total-N concentration mainly in summer season. It has been reported that N fertilizer applied to farmland is the main source of N pollution in surface water [71,72]. The distribution of ortho-P showed significant variation with average higher values (0.04 ± 0.002) in winter contrary to average lower values (0.02 ± 0.001) in summer season.…”
Section: Mak Vin Ash Wat Nin Spr Sum Aut Winmentioning
confidence: 89%
“…The sites located close to rural residential area showed higher mean total-N concentration mainly in summer season. It has been reported that N fertilizer applied to farmland is the main source of N pollution in surface water [71,72]. The distribution of ortho-P showed significant variation with average higher values (0.04 ± 0.002) in winter contrary to average lower values (0.02 ± 0.001) in summer season.…”
Section: Mak Vin Ash Wat Nin Spr Sum Aut Winmentioning
confidence: 89%
“…is nutrients sink and/or source within the system. This is due to the application of inorganic N fertilizer (ammonium bicarbonate) in the drainage basins and wastewater discharge (Cao et al, 2005;Sheldrick et al, 2003;Yan et al, 1999;Millennium Ecosystem Assessment, 2005). Phosphate concentrations in 13 rivers are at the pristine level (0.5 µM) and in 5 rivers are at average level (3 µM) compared to the global river data .…”
Section: Nutrients In the Chinese Estuariesmentioning
confidence: 99%
“…However, in the last few decades, human activities have caused enormous changes both in the nature and quantity of nutrient fluxes to oceans , of which the rapid increases of phosphate and nitrate inputs was well documented (Meybeck 1998;Yan et al, 1999;Liu et al, 2003;Yan et al, 2003;Biggs et al, 2004;Gächter et al, 2004;Duan et al, 2007), but the fluvial flux of DSi was found continuously decreasing in rivers worldwide (Justić et al, 1995;Conley et al, 2000;Humborg et al, 2000;Vörösmarty and Sahagian, 2000;Paul, 2003;Vörösmarty et al, 2003;Neal et al, 2005;Humborg et al, 2006;Duan et al, 2007;Li et al, 2007;Koszelnik and Tomaszek 2007;Roubeix et al, 2007).…”
Section: Introductionmentioning
confidence: 99%